KETERBUKAAN INFORMASI PUBLIK DALAM NEGARA HUKUM - Hasanuddin Hasim (Al-'Adl, 2018)
Information is the basic need of every person for personal development and social environment. Almost in every aspect of human life, starting from activities to fight for oneself and community groups to the implementation of government in the life of the nation and state, requires information. The concept of transparency and information is not only closely related to accountability but also with the rule of law in general. Both concepts can be seen as a necessary prerequisite for the successful participation of the general public in the life of the nation and state. Guaranteed freedom to obtain information can encourage the democratic process by opening up access to information to the public, so the people will be able to utilize available information to be critical in the process of public policy making, and in controlling the government, so that information monopolies do not occur. Law No. 14 of 2008 concerning Disclosure of Public Information is an effort to guarantee the right of everyone to obtain public information in order to encourage and improve the quality of community participation to provide input in public policy making. In the concept of the rule of law, what needs to be idealized is law, which then the law in the concept of state must be the foremost commander in regulating the pattern of life of the nation and state. The purpose of public information in the field of law is information created by public institutions tasked with promulgating legal products. These include primary legal sources such as regulation of legislation (regels) along with implementing regulations, decisions of state administration officials (beschickking), court decisions (verdicts) and or court decisions that have become jurisprudence, and policy rules (beleids- regels). With the concept of the rule of law which has been clarified by the existence of several developments regarding the rule of law, then Law No.14 / 2008 concerning Public Information Disclouser, is a way to embrace state propriety in guaranteeing human rights, both in groups, as well as individually.